2009
DOI: 10.1590/s0066-782x2009000900007
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade da frequência cardíaca, lípides e capacidade física de crianças obesas e não-obesas

Abstract: SummaryBackground: Obesity can affect the cardiac autonomic modulation, blood lipid levels and the physical capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
1
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 30 publications
(36 reference statements)
4
33
1
11
Order By: Relevance
“…Paschoal et al 22 also reported lower levels of HDL and increased triglycerides in obese children. The presence of such characteristics in children with obesity may be associated with changes in ANS activity as stated by Sekine et al 18 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Paschoal et al 22 also reported lower levels of HDL and increased triglycerides in obese children. The presence of such characteristics in children with obesity may be associated with changes in ANS activity as stated by Sekine et al 18 .…”
Section: Discussionmentioning
confidence: 91%
“…Yakinci et al 21 , using autonomic function tests, observed normal sympathetic activity and parasympathetic underactivity, and more recently, Kaufman et al 16 observed increase in LF/HF ratio and decreased HF index. Pascoal et al 22 found higher cardiac tone in the standing position when compared obese children with eutrophic children.…”
mentioning
confidence: 95%
“…27,28 Segundo estudo realizado com 30 crianças em Campinas, São Paulo, observou-se que a frequência cardíaca de crianças obesas em atividade física aumentava rapidamente em menos tempo de exposição ao esforço se comparado às crianças eutróficas, além das primeiras apresentarem capacidade física reduzida se comparado às últimas. 29 Assim, o excesso de peso pode dificultar atividades físicas, fazendo a criança obesa sentir-se inferior aos colegas, mais ágeis do que ela. 28 Vê-se então que as educadoras podem apresentar percepções errôneas quanto ao estado nutricional, mas corretas quanto aos fatores que colaboram para o excesso de peso, bem como sobre suas consequências deletérias, o que as motiva a empregar diversas estratégias na pré-escola, na tentativa de mudança nos hábitos das crianças.…”
Section: Ano Passado Por Exemplo Tinha Um Menininho Gordinho Aí Eu unclassified
“…Numerous studies have evaluated the effect of obesity and cardiac autonomic modulation (CAM) in children [14–28]. The majority of these studies have found that obesity impaired the balance of CAM towards a sympathetic overflow and reduced parasympathetic modulation in obese children.…”
Section: Introductionmentioning
confidence: 99%